Dietary Blueberry and Soluble Fiber Improve Serum Antioxidant and Adipokine Biomarkers and Lipid Peroxidation in Pregnant Women with Obesity and at Risk for Gestational Diabetes - Arpita Basu; Jeannette Crew; Jeffrey L. Ebersole; Jefferson W. Kinney; Arnold M. Salazar; Petar Planinic; James M. Alexander (Antioxidants, 2021)
Pregnancies affected by obesity are at high risk for developing metabolic complications with oxidative stress and adipocyte dysfunction contributing to the underlying pathologies. Few studies have examined the role of dietary interventions, especially those involving antioxidants including polyphenolic flavonoids found in fruits and vegetables on these pathologies in high-risk pregnant women. We conducted an 18 gestation-week randomized controlled trial to examine the effects of a dietary intervention comprising of whole blueberries and soluble fiber vs. control (standard prenatal care) on biomarkers of oxidative stress/antioxidant status and adipocyte and hormonal functions in pregnant women with obesity (n = 34). Serum samples were collected at baseline (<20 gestation weeks) and at the end of the study period (32–26 gestation weeks). Study findings showed maternal serum glutathione and antioxidant capacity to be significantly increased, and malondialdehyde to be decreased in the dietary intervention vs. control group (all p < 0.05). Among the adipokine biomarkers, serum plasminogen activator inhibitor-1 and visfatin, as biomarkers of adipocyte dysfunction and insulin resistance, were also decreased following dietary intervention (all p < 0.05). These findings support the need for supplementing maternal diets with berries and fiber to improve oxidative stress and risks of metabolic complications during pregnancy.